Extended thromboprophylaxis for hip or knee arthroplasty. Does the administration route and dosage regimen affect adherence? A cohort study (2020)
Purpose: Prevention of thromboembolic disease requires patients’ adherence to the extended thromboprophylaxis scheme. Oral anticoagulants are expected to improve adherence as a result of their route of administration; however, this assumption is yet to be confirmed. The purpose of this study was to assess the impact of the route of administration and dosage regimen on the compliance to the prescription. Materials and methods: This prospective cohort study included hip and knee arthroplasty patients who received pharmacological extended thromboprophylaxis with one daily injection, one daily oral tablet, or two daily oral tablets. A telephonic questionnaire was applied 35 days after the day of the surgery. Patients who omitted one or more doses of medication during the follow-up period were classified as “non-adherent.” Differences of adherence rates were assessed. Results: Five hundred and twenty patients were included: 153 received Apixaban (oral, twice a day), 155 Enoxaparin (injectable, once a day), and 212 Rivaroxaban (oral, once a day). Patients receiving oral once a day medication was more compliant compared with those who received an oral medication twice a day. Non-adherence rates were 3.2 and 9.2%, respectively (p = 0.033). No significant differences (p = 0.360) were found between oral once a day and injectable once a day medication. Conclusions: The number of daily doses prescribed was related to adherence to extended chemical prophylaxis, while the route of administration did not seem to have a significant impact. Strategies to promote outpatient compliance must be implemented, especially when regimes including more than one daily dose are prescribed. © 2019, SICOT aisbl.